Physico-chemical properties of new composite polymer for heat resistance with thin-film form through the blending of m-aramid and polyurethane (PU). (28th February 2018) - Ahn, Dajeong; Lee, Jaewoong; Kang, Chankyu
Abstract: Polymer composites can be applied to a variety of applications due to their ability to change material properties. This study suggests that blended m -aramid and polyurethane (PU) produces microporous structures in the form of thin-film. Changes in physico-chemical properties may have contributed to improved heat resistance properties. 2.5 wt% of plasticizer and DMAc were added to change the properties of the m- aramid/PU. After a brief wash, 0.08 mm m- aramid/PU in thin-film form was prepared. Scanning electron microscopy (SEM) and PMI capillary flow porometer showed the pore formation, size and distribution according to blending and coagulation bath condition, while Tg and peak shift using thermomechanical analyzer (TMA) and FT-IR observed the excellent blendability of m -aramid/PU without phase separation. The initial decomposition temperature (IDT) and Tm (melting temperature) showed higher thermal properties than pure PU. The heat resistance property of PU itself was improved with increasing m- aramid components. Graphical abstract: Highlights: m-aramid and PU showed sufficient miscibility without phase separation. When the concentration of DMAc increased from 10 wt% to 20 wt%, the permeability of liquid increased the greatest. The composition of DOP increased from 5 wt% to 10 wt%, the pore size increased significantly. As the composition of m-aramid increased, the Tg and Tm of m-aramid /PU blending film became higher than pure PU film. The initial degradation temperature (IDT) of m-aramid /PU blended films showed higher thermal properties than pure PU films.